Titi monkeys (Callicebus spp., Atelidae : Platyrrhini) in the Brazilian state of Rondonia - Ferrari, S. F.; Iwanaga, S.; Messias, M. R.; Ramos, E. M.; Ramos, PCS; Neto, EHD; Coutinho, PEG (Japan Monkey Centre, 2000)
Five species of titi monkey (Callicebus brunneus, Callicebus caligatus, Callicebus cinerascens, Callicebus donacophilus, and Callicebus moloch) were recorded in surveys of primate populations at 26 sites throughout the Brazilian state of Rondonia. The distribution of the two species, C. cinerascens and C. donacophilus (recorded in the state for the first time), appeared to be related to that of non-forest ecosystems, the former in the cerrado woodlands, and the latter in gallery forests of the Guapore grasslands. The results of the surveys also indicate that C. brunneus has a more restricted distribution in southern Rondonia than was previously thought, whereas C. moloch is more widespread. However, the ecological factors that determine species distribution in the south of the state remain unclear on the basis of the available data. All species were observed in small social groups of no more than five individuals, which are typical of the genus, generally in the middle and lower forest strata.
Keywords: Callicebus; species diversity; population; zoogeography; Amazonia